Management of Patients with ST-Segment Elevation Myocardial Infarction during the COVID-19 Pandemic - Yildirim, Arafat; Ozcan Abacioglu, Ozge; Kilic, Salih; Demir, Serafettin (European Journal of Therapeutics, 2021)
Objective: Elective operations had to be postponed due to the COVID-19 pandemic that emerged in the last quarter of 2019 and affected the whole world in a short time. However, for emergencies such as myocardial infarction (MI), unfortunately, this is not possible. We aimed to evaluate the management of ST-segment elevation myocardial infarction (STEMI) before and during the COVID-19 pandemic. Methods: One hundred and eleven consecutive patients with STEMI between April 2020 and May 2020 and 149 patients with STEMI 1 year before the pandemic in the same period were included in the study. Groups were compared in terms of the treatments applied, pre–post-dilatation, duration of the procedure, hospitalization, and the primary end-point. Death due to MI or complications of MI was the primary end-point. Results: The mean age of the patients was 59.7 6 12.3 (n ¼ 195 [75%] male). The two groups were similar in terms of gender, diabetes mellitus, hypertension, hyperlipidemia, smoking, and laboratory results. Although the median duration of the door balloon in the pandemic was similar (39 and 37 minutes, respectively; P ¼ .342), the procedure times were shorter, the mean total hospitalization times were longer, and the differences were statistically significant (P ¼ .022 and <.001, respectively). In the study group, 68 patients had predilatation and 30 had post-dilatation during the procedure. The two groups were similar in terms of the primary end-point (P ¼ .196). Conclusion: Percutaneous intervention should be the routine procedure to STEMI patients during the pandemic period, despite the positive possibility of COVID-19 and the risk of transmission.